Repeated games played in a network - Markus Kinateder (Fondazione Eni Enrico Mattei (FEEM), 2008)
Delayed perfect monitoring in an infinitely repeated discounted game is modelled by allocating the players to a connected and undirected network. Players observe their immediate neighbors' behavior only, but communicate over time the repeated game's history truthfully throughout the network. The Folk Theorem extends to this setup, although for a range of discount factors strictly below 1, the set of sequential equilibria and the corresponding payoff set may be reduced. A general class of games is analyzed without imposing restrictions on the dimensionality of the payoff space. Due to this and the bilateral communication structure, truthful communication arises endogenously only under additional conditions. The model also produces a network result; namely, the level of cooperation in this setup depends on the network's diameter, and not on its clustering coefficient as in other models.
Keywords: C72; C73; D85; 330; Repeated Game; Delayed Perfect Monitoring; Network; Communication; Wiederholte Spiele; Gleichgewicht; Asymmetrische Information; Folk-Theorem; Spieltheorie